2008
DOI: 10.1007/s10620-008-0537-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Progression of Endoscopic Barrett’s Epithelium in Japan: A Multivariate Analysis Based on the Prague C & M Criteria

Abstract: Forty-three percent of the total study population was diagnosed as having endoscopic Barrett's epithelium. During the follow-up period, 12.6% of the cases with Barrett's epithelium exhibited progression which was associated with aging and severe erosive esophagitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 27 publications
6
37
0
Order By: Relevance
“…These findings are consistent with previous reports from Japan indicating that SSBE is more common while LSBE is rarer, compared with observations reported in the United States and Western Europe [21,22]. The frequency of BE may be affected by differences in its definition, and particularly by whether the presence of intestinal metaplasia is essential for making the diagnosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with previous reports from Japan indicating that SSBE is more common while LSBE is rarer, compared with observations reported in the United States and Western Europe [21,22]. The frequency of BE may be affected by differences in its definition, and particularly by whether the presence of intestinal metaplasia is essential for making the diagnosis.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we selected control subjects from among outpatients who had undergone endoscopies for a health check-up during the same period and who had no endoscopically identified localized lesions in the upper gastrointestinal tract. Nonetheless, the prevalences of the endoscopic findings, including EE and BE, in the controls were similar to those described for Japanese populations in previous reports [21,22]. Hence, a bias in the selection of controls is unlikely, although a prospective cohort study is required to resolve this issue.…”
Section: Discussionsupporting
confidence: 81%
“…1). 26,27 However, the different definitions used for the esophagogastric junction (EGJ) might, to a large extent, account for this discrepancy. Most studies conducted in Asia outside of Japan defined the proximal margin of gastric folds as the EGJ, whereas the Japanese studies used the distal margin of the palisade vessels as the EGJ landmark 35…”
Section: Lower Prevalence Of Barrett Esophagus In Asiamentioning
confidence: 99%
“…Simple obesity, as measured by the body mass index (BMI), has been reported as one of the strongest risk factors for GERD symptoms, erosive esophagitis and esophageal adenocarcinoma [6,7,8,9,10], while it still remains controversial whether it is also an independent risk factor for BE [11,12,13,14,15]. Several studies have examined the association between simple obesity and BE and inconsistent results have been reported, ranging from a significantly increased risk associated with a high BMI [11,12], to a significantly increased risk associated with a high BMI only in the presence of GERD symptoms [13], to no association at all [14].…”
Section: Simple Obesity and The Risk Of Bementioning
confidence: 99%
“…Several studies have examined the association between simple obesity and BE and inconsistent results have been reported, ranging from a significantly increased risk associated with a high BMI [11,12], to a significantly increased risk associated with a high BMI only in the presence of GERD symptoms [13], to no association at all [14]. Our retrospective cohort study in the Japanese general population showed that simple obesity is not a risk factor for BE; the evaluation of the association between BMI and BE may be limited by the small numbers of obese subjects in the Japanese general population (table 1) [15]. …”
Section: Simple Obesity and The Risk Of Bementioning
confidence: 99%